Providing military formations with human resources in peace time under conditions of limited financing - Medvid, М. М. (Honor and Law, 2019)
The mechanism of providing the military formations with human resources in peace time under conditions of limited financing and state transformation into market economy is proved. The considered mechanism gives the possibility to avoid regional disproportions in recruiting the military personnel on the contract basis.